Superluminous Supernovae at High Redshift. (6th March 2017) - Abbott, Tim; Cooke, Jeff; Curtin, Chris; Joudaki, Shahab; Katsianis, Antonios; Koekemoer, Anton; Mould, Jeremy; Tescari, Edoardo; Uddin, Syed; Wang, Lifan
Abstract: Superluminous supernovae are beginning to be discovered at redshifts as early as the epoch of reionisation. A number of candidate mechanisms is reviewed, together with the discovery programmes.